Dirty beasts - Dahl, Roald, 1916-1990.; Blake, Quentin (New York, N.Y., U.S.A. : Puffin Books, 1986)
A collection of humorous poems about amazing or nasty creatures, including a flying cow, a pig who turns the tables on a farmer, and crocodiles, lions, and anteaters who delight in devouring people.
4.0
3-6
Keywords: Animals -- Juvenile poetry; Children's poetry, English; Animals -- Poetry; English poetry; Humorous poetry; Animals -- Poetry